2019
DOI: 10.1523/eneuro.0005-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Regional Brainstem Diffusion Imaging Measures of Microstructure across the Migraine Cycle

Abstract: The neural mechanisms responsible for the initiation and expression of migraines remain unknown. Although there is growing evidence of changes in brainstem anatomy and function between attacks, very little is known about brainstem function and structure in the period immediately prior to a migraine. The aim of this investigation is to use brainstem-specific analyses of diffusion weighted images to determine whether the brainstem pain processing regions display altered structure in individuals with migraine acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 55 publications
3
30
0
Order By: Relevance
“…This study therefore suggests a pre-headache sensitivity to pain, or reduced threshold to pain, during the migraine attack (and therefore a susceptibility to exogenous triggers) and the subsequent implication of altered or dysfunctional endogenous pain modulation within the pain network in the brain during the migraine attack or cycle, which may be responsible for the sensation of pain felt following premonitory symptoms. The same authors have also recently demonstrated possible structural changes in similar brain areas (dorsolateral pons, periaqueductal gray, and spinal trigeminal nuclei) within 24 h of a migraine attack using mean diffusivity and fractional anisotropy (41).…”
Section: Functional Mrimentioning
confidence: 92%
“…This study therefore suggests a pre-headache sensitivity to pain, or reduced threshold to pain, during the migraine attack (and therefore a susceptibility to exogenous triggers) and the subsequent implication of altered or dysfunctional endogenous pain modulation within the pain network in the brain during the migraine attack or cycle, which may be responsible for the sensation of pain felt following premonitory symptoms. The same authors have also recently demonstrated possible structural changes in similar brain areas (dorsolateral pons, periaqueductal gray, and spinal trigeminal nuclei) within 24 h of a migraine attack using mean diffusivity and fractional anisotropy (41).…”
Section: Functional Mrimentioning
confidence: 92%
“…Local Institutional Human Research Ethics Committees approved the study, and we obtained informed written consent from each subject for all procedures according to the Declaration of Helsinki. Data from 28 of the 34 migraineurs and 12 of the control subjects were used in previous studies (1012), as well as data from 23 of the 34 migraineurs and 12 of the control subjects in our previous study (9).…”
Section: Methodsmentioning
confidence: 99%
“…This study was approved by the Institutional Human Research Ethics Committee at the University of Sydney and informed written consent was obtained for all participants in accordance with the Declaration of Helsinki. Data from 30 of the 39 migraineurs were used in previous investigations [17][18][19][20].…”
Section: Subjectsmentioning
confidence: 99%